Analisis SWOT: Peran Dan Tantangan Toko Sembako Suci Dalam Menghadapi Persaingan Digital - Rani Indriani; Putri Nayla; Anisatul Faradila Suci; Pupung Purnamasari (GLOBAL SCIENTS PUBLISHER, 2025)
Grocery stores have an important role in supporting the local economy and meeting the basic needs of the community. This study aims to analyze the role and challenges of Toko Sembako Suci in facing market competition in the East Cikarang area through a SWOT analysis approach. The research method used is a qualitative approach with case study techniques, observation, interviews, and documentation. The results show that this store has several strengths such as strategic location, lower prices, personalized service, and QRIS digital payment. However, the store also faces weaknesses in manual stock management, limited capital, and lack of digital marketing. Based on the results of the SWOT analysis, a development strategy was formulated in the form of operational digitalization, development of delivery services, access to training programs and capital from the government, and cooperation with local suppliers. This research provides strategic recommendations to improve the competitiveness of similar MSMEs in facing modern market competition..